"Authentic" digital inclusion? Dis/ability performances on social media by users with concealable communicative disabilities. (February 2022) - Bitman, Nomy
Despite the increased technical accessibility of social media, disabled users' attempts to be socially included are still understudied. These users' agency-based choices are impacted by constant able-bodied surveillance and disciplining, especially when it comes to dis/ability visibility and potential context collapse. This paper develops the concept of disability performance within social media studies, presenting a qualitative study of social media users with concealable communicative disabilities: autistics, hard-of-hearing and people who stutter. Four factors were found to shape users' dis/ability performances: the use of social media interfaces for the compartmentalization of disabled identity; users' continuous efforts to make their social environment inclusionary; the centrality of users' disabled identity and intersectionality; and the design of the performance's message . Together, these show disability performances to be deliberate expressions of agency on the part of vulnerable social media users, who perform dis/ability according to their own evaluation of authenticity to increase their social inclusion.